Electric field in an AC dielectric barrier discharge overlapped with a nanosecond pulse discharge. (14th June 2016) - Goldberg, Benjamin M; Shkurenkov, Ivan; Adamovich, Igor V; Lempert, Walter R
Abstract: The effect of ns discharge pulses on the AC barrier discharge in hydrogen in plane-to-plane geometry is studied using time-resolved measurements of the electric field in the plasma. The AC discharge was operated at a pressure of 300 Torr at frequencies of 500 and 1750 Hz, with ns pulses generated when the AC voltage was near zero. The electric field vector is measured by ps four-wave mixing technique, which generates coherent IR signal proportional to the square of electric field. Absolute calibration was done using an electrostatic (sub-breakdown) field applied to the discharge electrodes, when no plasma was generated. The results are compared with one-dimensional kinetic modeling of the AC discharge and the nanosecond pulse discharge, predicting behavior of both individual micro-discharges and their cumulative effect on the electric field distribution in the electrode gap, using stochastic averaging based on the experimental micro-discharge temporal probability distribution during the AC period. Time evolution of the electric field in the AC discharge without ns pulses, controlled by a superposition of random micro-discharges, exhibits a nearly 'flat top' distribution with the maximum near breakdown threshold, reproduced quite well by kinetic modeling. Adding ns pulse discharges on top of the AC voltage waveform changes the AC discharge behavior in a dramatic way, inducing transition from random micro-discharges to a more regular, near-1D discharge. In this case, reproducible volumetric AC breakdown is produced at a well-defined moment after each ns pulse discharge. During the reproducible AC breakdown, the electric field in the plasma exhibits a sudden drop, which coincides in time with a well-defined current pulse. This trend is also predicted by the kinetic model. Analysis of kinetic modeling predictions shows that this effect is caused by large-volume ionization and neutralization of surface charges on the dielectrics by ns discharge pulses. The present work demonstrates that this effect may be used to control the phase of AC barrier discharges, triggering reproducible breakdowns at well-defined moments.